Framingham Heart Study 100K Project: genome-wide associations for blood pressure and arterial stiffness - Newton-Cheh Christopher; Benjamin Emelia J; Larson Martin G; Levy Daniel; Wang Thomas J; Hwang Shih-Jen; Vasan Ramachandran S; Mitchell Gary F (BMC, 2007)
Abstract Background About one quarter of adults are hypertensive and high blood pressure carries increased risk for heart disease, stroke, kidney disease and death. Increased arterial stiffness is a key factor in the pathogenesis of systolic hypertension and cardiovascular disease. Substantial heritability of blood-pressure (BP) and arterial-stiffness suggests important genetic contributions. Methods In Framingham Heart Study families, we analyzed genome-wide SNP (Affymetrix 100K GeneChip) associations with systolic (SBP) and diastolic (DBP) BP at a single examination in 1971-1975 (n = 1260), at a recent examination in 1998-2001 (n = 1233), and long-term averaged SBP and DBP from 1971-2001 (n = 1327, mean age 52 years, 54% women) and with arterial stiffness measured by arterial tonometry (carotid-femoral and carotid-brachial pulse wave velocity, forward and reflected pressure wave amplitude, and mean arterial pressure; 1998-2001, n = 644). In primary analyses we used generalized estimating equations in models for an additive genetic effect to test associations between SNPs and phenotypes of interest using multivariable-adjusted residuals. A total of 70,987 autosomal SNPs with minor allele frequency ≥ 0.10, genotype call rate ≥ 0.80, and Hardy-Weinberg equilibrium p ≥ 0.001 were analyzed. We also tested for association of 69 SNPs in six renin-angiotensin-aldosterone pathway genes with BP and arterial stiffness phenotypes as part of a candidate gene search. Results In the primary analyses, none of the associations attained genome-wide significance. For the six BP phenotypes, seven SNPs yielded p values < 10-5. The lowest p-values for SBP and DBP respectively were rs10493340 (p = 1.7 × 10-6) and rs1963982 (p = 3.3 × 10-6). For the five tonometry phenotypes, five SNPs had p values < 10-5; lowest p-values were for reflected wave (rs6063312, p = 2.1 × 10-6) and carotid-brachial pulse wave velocity (rs770189, p = 2.5 × 10-6) in MEF2C, a regulator of cardiac morphogenesis. We found only weak association of SNPs in the renin-angiotensin-aldosterone pathway with BP or arterial stiffness. Conclusion These results of genome-wide association testing for blood pressure and arterial stiffness phenotypes in an unselected community-based sample of adults may aid in the identification of the genetic basis of hypertension and arterial disease, help identify high risk individuals, and guide novel therapies for hypertension. Additional studies are needed to replicate any associations identified in these analyses.